Microbiology Of Nosocomial Infection In Tertiary Hospitals Of Dhaka City And Its Impact (Bangladesh Journal of Medical Microbiology, 2012)
Nosocomial infection is an endemic problem encountered in hospitalized patients all over the world including Bangladesh. The present prospective study was carried out on 152 patients who were admitted in Dhaka Medical College Hospital and BIRDEM Hospital over a two years period to determine the organisms responsible for nosocomial infection, their antibiotic susceptibility pattern, sources and the impact of hospital infection on patient management. Samples were collected from postoperative wounds, post catheterized urinary tract infection (UTI) and diabetic wounds. The patients without postoperative wound infection were taken as control group. To trace the sources of infection the samples from the different objects of the hospital environment were studied. The collected samples were cultured and isolated organisms were identified by colony morphology, gram staining and necessary biochemical tests. The identified organisms were tested for antibiogram pattern and plasmid profile. The predominating organisms responsible for nosocomial infection were Esch.coli (55.9%). The other organisms were Pseudomonas sp. (33.3%), Proteus sp. (12.7%), Staphylococcus aureus (5.9%), Klebsiella sp. (4.9%) and Acinatobacter sp. (3.9%). The isolated organism showed high level of resistance to commonly used antibiotics. The resistance of the organisms markedly increased with the hospital stay. The hospital stay of the infected cases was significantly (p